2018
DOI: 10.3952/physics.v58i3.3814
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobility fluctuations due to the capture–emission process

Abstract: It is shown that the free charge carrier capture–emission process causes both the charge carrier density and mobility fluctuations. In this report we present the calculation results in order to find how the capture–emission process affects the free charge carrier mobility and mobility fluctuations. The carrier mobility dependence on phonon, impurity and carrier–carrier scatterings, and the mobility dependence on the electric field and the energy gap variation due to the doping level were taken into account. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Low-frequency electrical fluctuations of the group B LDs are distinguished by 1/ f α -type spectra in the entire investigated current region, where index α ranges from 0.9 to 1.4 ( Figure 5 a). In semiconductor devices, the 1/ f α -type fluctuations originate from the superposition of Lorentzian-type spectra due to different charge carrier generation-recombination or capture-emission processes having wide distribution of relaxation times [ 19 , 20 , 21 ]. The electrical noise spectra of group A LDs, as it can be seen from Figure 5 b, are also 1/ f α -type in a forward current range up to the second bump.…”
Section: Resultsmentioning
confidence: 99%
“…Low-frequency electrical fluctuations of the group B LDs are distinguished by 1/ f α -type spectra in the entire investigated current region, where index α ranges from 0.9 to 1.4 ( Figure 5 a). In semiconductor devices, the 1/ f α -type fluctuations originate from the superposition of Lorentzian-type spectra due to different charge carrier generation-recombination or capture-emission processes having wide distribution of relaxation times [ 19 , 20 , 21 ]. The electrical noise spectra of group A LDs, as it can be seen from Figure 5 b, are also 1/ f α -type in a forward current range up to the second bump.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [18], it is demonstrated that the charge carrier capture-emission process is the main source of the low-frequency noise in homogeneous semiconductors and this process can produce the free charge carrier mobility fluctuations in particular cases [19].…”
Section: Introductionmentioning
confidence: 99%